The Current State of Distributed Renewable Generation, Challenges of Interconnection and Opportunities for Energy Conversion based DC Microgrids - Ullah, Shahid; Haidar, Ahmed M.A.; Hoole, Paul R.; Hushairi, Zen; Ahfock, Tony (Elsevier Ltd., 2020)
As distributed renewable energy sources (RES) continue to expand, the necessity arises for more robust coordination approaches and conversion techniques to tackle the challenges introduced by uncertainties in renewable generation. Increasing concerns about energy efficiency and power grid security, such as the significant number of conversion stages for energy production from renewable resources and the bidirectional power flow in the distribution system, have attracted attention to the topic. The presented comprehensive review in this paper discusses the merits and weaknesses of different integration strategies as supported by the literature review. In particular, the focus is placed on the challenges of interconnection and opportunities for direct current (DC) systems. The ultimate objective of this paper is to explore the most important power grid-wide effects due to the expected renewable energy expansion and to gain insights on the availability characteristics of DC microgrids to facilitate their integration with the power grid. The idea behind this is to establish inferences that energy conversion based DC microgrids can be a possible solution to mitigate the negative effect of renewable energy expansion. This is accomplished by systematically reviewing studies on power grid integration as well as providing technical analysis of the resulting outcomes in relation to the general impact of renewable energy production, and then, conducting a comparative study on renewable energy conversion based DC and alternating current (AC) systems. The types of bus topologies and control of DC distribution systems are also intensively reviewed and discussed. Moreover, the protection design considerations, control classifications and standards of DC microgrids are highlighted to explore the future research trends to be undertaken. The review concluded that the impact of interconnection on power grid can be eliminated through the use of intelligent control with advance communication technologies and the implementation of DC microgrids powered by sustainable resources in the distribution system.